Emotional Balance and Its Relation with Self – Confidence for Special Education Students Department - Mohammed Saeed Al-Brifkani, Khawla Ahmed (Opción, 2019)
The aim of the current research is to investigate emotional balance and its relation with self . Confidence for special education students . The research- er adopted descriptive style due to its appropriateness . The sample was (80) students divided in to (60) pupils in first year an (20) of fourth year . The researcher depended on ready – made scale of emotional balance made by ( Al-Masoudi 2002) . The scale consisted of (60) items with (4) alternatives : ( always – usually – sometimes – rarely ) respectively . The researcher made a survey of self – confidence with (30) items with three alternatives : (a lot – sometimes – rarely ) respectively . The researcher used the following statistical methods ( Pearson Conjunction factor – T. test of an independent sample and two independent samples Spearman – Brown formula ) . The re- search resulted in : 1- Emotional balance level of the students was high .. 2- Self – Confidence level of the students was high. 3- Existence of a positive exaggeration relation between emotional balance and self – confidence . The more emotional balance increases , the self – confidence increases as well . Given these findings the researcher made a number of recommendations and suggestions , to mention but few co enhance role of educational supervision in encouraging students to keep emotional balance and invest it in partici- pating in practical activities. The most important suggestion is to make a study on emotional balance and its relation with personal features for the students of basic education college